2018
DOI: 10.1002/bjs.10762
|View full text |Cite
|
Sign up to set email alerts
|

Eight-year follow-up of a randomized clinical trial comparing ultrasound-guided foam sclerotherapy with surgical stripping of the great saphenous vein

Abstract: Surgical stripping had a technically better outcome in terms of recurrence of GSV and SFJ reflux than UGFS in the long term. Long-term follow-up suggests significant clinical progression of venous disease measured by VCSS in both groups, but less after surgery. Registration number: NCT02304146 (http://www.clinicaltrials.gov).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 20 publications
(20 reference statements)
1
10
0
2
Order By: Relevance
“…173 An eight-year randomized comparative trial published in 2018 showed that stripping compared to sclerotherapy of the GSV led to a better anatomical success and less symptoms recurrence, yet with no significant differences at the EQ-5D standardized measure of health status. 174 On this topic, in 2019, Kalodiki et al published a discord outcome analysis comparing endovenous laser ablation and foam sclerotherapy for GSV reflux treatment, including evaluation of change in Aberdeen Varicose Veins Questionnaire (AVVQ), Venous Clinical Severity Score (VCSS) and Venous Filling Index (VFI). Interestingly, at 68 months, no significant differences in VCSS and VFI were found, while the laser group had an improvement in AVVQ.…”
Section: Significant New Data Reported At the Meetingmentioning
confidence: 99%
See 1 more Smart Citation
“…173 An eight-year randomized comparative trial published in 2018 showed that stripping compared to sclerotherapy of the GSV led to a better anatomical success and less symptoms recurrence, yet with no significant differences at the EQ-5D standardized measure of health status. 174 On this topic, in 2019, Kalodiki et al published a discord outcome analysis comparing endovenous laser ablation and foam sclerotherapy for GSV reflux treatment, including evaluation of change in Aberdeen Varicose Veins Questionnaire (AVVQ), Venous Clinical Severity Score (VCSS) and Venous Filling Index (VFI). Interestingly, at 68 months, no significant differences in VCSS and VFI were found, while the laser group had an improvement in AVVQ.…”
Section: Significant New Data Reported At the Meetingmentioning
confidence: 99%
“…An eight-year randomized comparative trial published in 2018 showed that stripping compared to sclerotherapy of the GSV led to a better anatomical success and less symptoms recurrence, yet with no significant differences at the EQ-5D standardized measure of health status. 174…”
Section: Sclerotherapy For Varicose Veinsmentioning
confidence: 99%
“…Angaben zu Ausschlusskriterien, wie z. B. insuffiziente Vena accessoria der VSM [20], oder zusätzlichen Eingriffen, wie Phlebektomie oder Perforansligatur, sind in der Analyse nicht berücksichtigt.…”
Section: Ergebnisseunclassified
“…Crosseninsuffizienz lag nach UGFS bei 65,8 % und nach HL + CS bei 41,7 % (p = 0,001) vor. Rezidiv-Reflux oberhalb des Knies trat nach UGFS (72,55 %) häufiger als nach HL + CS (20,4 %; p = 0,001) auf [20].…”
Section: Ergebnisse Der Chirurgischen Behandlungunclassified
“…Out of these STD and polidocanol (POL) are safe and most commonly used. [2][3][4][5][6] In this study we have compared early outcomes in patients having any one of these two sclerosants viz. STD and POL in the treatment of varicosities of tributaries of GSV and SSV.…”
mentioning
confidence: 99%